Acetate and Bicarbonate Assimilation and Metabolite Formation in Chlamydomonas reinhardtii: A 13C-NMR Study - Singh, Himanshu; Shukla, Manish R.; Chary, Kandala V. R.; Rao, Basuthkar J. (PLOS ONE, 2014)
Cellular metabolite analyses by 13C-NMR showed that C. reinhardtii cells assimilate acetate at a faster rate in heterotrophy than in mixotrophy. While heterotrophic cells produced bicarbonate and CO2aq, mixotrophy cells produced bicarbonate alone as predominant metabolite. Experiments with singly 13C-labelled acetate (13CH3-COOH or CH3-13COOH) supported that both the 13C nuclei give rise to bicarbonate and CO2aq. The observed metabolite(s) upon further incubation led to the production of starch and triacylglycerol (TAG) in mixotrophy, whereas in heterotrophy the TAG production was minimal with substantial accumulation of glycerol and starch. Prolonged incubation up to eight days, without the addition of fresh acetate, led to an increased TAG production at the expense of bicarbonate, akin to that of nitrogen-starvation. However, such TAG production was substantially high in mixotrophy as compared to that in heterotrophy. Addition of mitochondrial un-coupler blocked the formation of bicarbonate and CO2aq in heterotrophic cells, even though acetate uptake ensued. Addition of PSII-inhibitor to mixotrophic cells resulted in partial conversion of bicarbonate into CO2aq, which were found to be in equilibrium. In an independent experiment, we have monitored assimilation of bicarbonate via photoautotrophy and found that the cells indeed produce starch and TAG at a much faster rate as compared to that in mixotrophy and heterotrophy. Further, we noticed that the accumulation of starch is relatively more as compared to TAG. Based on these observations, we suggest that acetate assimilation in C. reinhardtii does not directly lead to TAG formation but via bicarbonate/CO2aq pathways. Photoautotrophic mode is found to be the best growth condition for the production of starch and TAG and starch in C. reinhardtii.